Characterization, Hypoglycemic Activity, and Antioxidant Activity of Methanol Extracts From Amomum tsao-ko: in vitro and in vivo Studies - Xie, Libin; Yu, Dan; Li, Yanan; Ju, Huidong; Chen, Jia; Hu, Lianxia; Yu, Longquan (Frontiers in Nutrition, 2022)
The dried fruit of Amomum tsao-ko is well-known as a spice as well as a Chinese traditional herb. This study aimed to identify the bioactive constituents in the powder of methanol extract from Amomum tsao-ko (PMEAT), and to evaluate the hypoglycemic and antioxidant effects of PMEAT, in vitro and in vivo. We identified 36 phytochemicals in PMEAT by employing HPLC-MS/MS. PMEAT solution was found to have potent α-glucosidase-inhibiting activity (IC50, 0.145 mg/mL) in vitro, twice as strong as that of acarbose (IC50, 0.273 mg/mL). To investigate the hypoglycemic activity of PMEAT in vivo, we studied the impact of low-dose PMEAT (the addition of 100mg/kg PMEAT to the mice diet) and high-dose PMEAT (200mg/kg PMEAT addition) treatments in STZ-induced diabetic mice. After six weeks of intervention, significantly decreased fasting blood glucose (FBG) (p < 0.05), significantly decreased area under the curve (AUC) of the oral glucose tolerance test (p < 0.05), significantly decreased HOMA-IR (p < 0.05), and significantly increased HOMA- (p < 0.05), were observed in the high-dose PMEAT group. Moreover, we performed an antioxidant activity experiment in vitro. The results showed that PMEAT had a strong ability to scavenge DPPH (IC50, 0.044mg/mL) as well as ABTS free radicals (IC50, 0.040mg/mL). In an animal experiment conducted on oxidative damage mice model which was induced by D-glucose and high-fat diet, we observed significantly increased dismutase (SOD) (p<0.01), glutathione (GSH) (p<0.01), and glutathione peroxidase (GSH-Px) (p<0.01), and significantly reduced malondialdehyde (MDA) and 8-ISO-prostaglandin-PGF2α (8-ISO-PGF2α), after treatment with PMEAT for 90 days. In conclusion, this study reveals the therapeutic potential of Amomum tsao-ko for the treatment of diabetes and helps us discover new antioxidant candidates from natural sources.